Effect of Stocking Density on Feed Efficiency of Caged Broilers under Hot Climatic Conditions - Nutan Kumari; Ramesh Pandey; Neeraj; Ram Pal Singh; Anand Kumar Singh; Gaurav Ugale (Archives of Current Research International, 2025)
The present study investigates the effect of stocking density on feed consumption and feed conversion ratio (FCR) in caged broilers under hot climatic conditions. A total 72 day-old broiler chicks, were randomly distributed in three groups as treatments of stocking density which, were further subdivided into eight sub-group to serve as replicates. The broiler chicks in different treatments of the stocking density at 1 sq. ft. per chick, 1.33 sq. ft. per chick and 2 sq. ft. per chick were evaluated. The results revealed that stocking density did not have any significant impact on the feed consumption and feed conversion ratio (FCR). However, a trend showed that broilers at moderate stocking density (1.33 sq. ft. per chick) supported the better feed utilization. These findings are in agreement with several studies which reported non-significant impact of stocking density on feed intake and FCR. While higher stocking densities may raise issues related to heat stress during summer season, the present experiment suggests that with proper heat stress and pre-summer management practices, good performance may be obtained, across different stocking densities. Effective management practices are essential for enhancing the feed efficiency and bird welfare in hot climates. This experiment highlights the importance of balancing stocking density and environmental conditions to achieve sustainable broiler production.